Evaluation of Mordanting Methods and Natural Dye Extraction from Mangosteen Peel for Fibre-Dyeing Applications Using Different Solvents - Muhamad, Aida; Aina Naylisa Uyop; Ayu Zulaikha Idham Kadri; Aliya Nabila Mohammad Raswan (Multidisciplinary Applied Research and Innovation, 2026)
Developing textile dyeing processes using natural products such as fruits is one way to promote sustainability in manufacturing. This research focuses on extracting natural dyes from mangosteen (Garnicia mangostana L.) peel waste for cotton fabric dyeing. The extraction was carried out using four different solvent systems: distilled water, 50% ethanol, 1% citric acid, and a mixture of 50% ethanol with 1% citric acid. Among these, ethanol yielded the highest anthocyanin content at 193.9 ppm, followed by ethanol + citric acid at 174.6 ppm, citric acid at 64.2 ppm, and distilled water at 48.8 ppm. The purpose of testing different solvents was to evaluate their effectiveness in extracting natural dyes from mangosteen peels. Extraction was performed using the air-drying method for all four solvents, followed by a mordanting process with zinc sulfate through three approaches: pre-mordanting, simultaneous mordanting, and post-mordanting. To confirm the presence of anthocyanins in mangosteen peel, UV-Vis and FTIR spectroscopy analyses were conducted. To assess colour fastness, two tests were performed: washing fastness and light fastness under sunlight. The vibrancy score for post-mordanting with ethanol was the highest at 22.8, indicating brighter and more attractive dyeing on cotton fabric. However, in terms of light fastness, pre-mordanting with distilled water and ethanol performed best, with scores of 8.37 and 9.11, respectively. Overall, post-mordanting with ethanol demonstrated superior dye absorption and colour vibrancy, while pre-mordanting provided greater resistance to colour fading under sunlight.